Karakterisasi Senyawa Utama Ekstrak Daun Aglaia elliptica Blume dan Uji Sitotoksisitas pada Sel Kanker Payudara - AGUNG ERU WIBOWO; FRANS SUYATNA; WAHONO SUMARYONO; NURYATI CHAERANI SIREGAR (JURNAL ILMU KEFARMASIAN INDONESIA, 2009)
AIglaia elliptica Blume is one of plant species from the genus of Aglaia, belonging to the family of Meliaceae. This group of plants is known to have powerful cytotoxic effect. This research was conducted to isolate and characterize major compound(s) from ethanol extract of Aglaia elliptical leaf that can be used as marker compound(s) for extract standardization. Approximately 1000 g of Aglaia elliptica Blume leaf dry powder was extracted with ethanol using maceration method. Ethanol extract was then fractionated using n-hexane and ethyl acetate. Six sub-fractions were obtained from the Vacuum Liquid Chromatography (VLC) process of ethyl acetate fraction. Based on the HPLC profile and separation process using column chromatography and preparative HPLC, a major compound (with the weight of 36.80 mg) was successfully isolated from sub-fraction H. Analyses on its UV absorbance pattern, mass spectra, and proton NMR identified the isolated compound as a compound with molecular weight of 300, C18H24N2O2, known as odorin. Cytotoxicity test showed that odorin has inhibition effect against MCP-7 cell line with IC5O of 153.32 ppm.